Toner and method for producing the same
By using amino resin and crystalline polyester resin in the toner and adding an appropriate amount of boric acid during the manufacturing process, the problem of high temperature deviation and uneven droplet in the recording material when improving low temperature fixity is solved, and excellent fixity and high temperature deviation resistance are achieved.
Patent Information
- Application Number
- JP2021123717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-28
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-07-28
AI Technical Summary
When the existing-toner improves the low-temperature fixity, high-temperature offset and uneven dropping of recording materials are prone to problems.
A toner containing amino resin and crystalline polyester resin is used, and boric acid is added during the manufacturing process to control the content of the crystalline polyester resin between 30.00% and 80.00% and the content of the boric acid is between 0.10% and 10.00%.
The excellent fixity of the toner under low temperature conditions is achieved, while avoiding the problems of high temperature offset and uneven droplet in the recording material, and improving the resistance to high temperature offset and gloss uniformity of the toner.
Smart Images

Figure 0007665467000010 
Figure 0007665467000001 
Figure 0007665467000002
Abstract
Description
[Technical field]
[0001] SUMMARY This disclosure relates to toners and methods of making toners for developing electrostatic images used in imaging processes such as electrophotography and electrostatic printing. [Background technology]
[0002] In recent years, there has been an increasing demand for energy saving in copying machines and printers, and in particular, attempts have been made to achieve energy saving by lowering the fixing temperature, and toners are required to have low-temperature fixing properties that enable fixing at lower temperatures.
[0003] As an example of improving low-temperature fixing property, the use of a crystalline material as a binder resin has been proposed. Patent Document 1 proposes a toner with excellent low-temperature fixing property by using a crystalline polyester resin having sharp melting property as a binder resin.
[0004] On the other hand, when low-temperature fixability is improved, the storage characteristics of the toner may be deteriorated, and problems may arise such as heat resistance during transportation and filming on printer parts. Toners having a core-shell structure have been proposed to achieve both low-temperature fixability and storage characteristics. Patent Document 2 proposes a toner having a core-shell structure and containing a borax coupling agent between the core and shell. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-159001 A [Patent Document 2] Special Publication No. 2015-506494 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in Patent Document 1, when the content of the crystalline polyester resin is increased to further improve the low-temperature fixability, high-temperature offset is likely to occur. Also, in Patent Document 2, when the crystalline polyester resin is contained, the crystalline polyester resin melts during fixing, causing uneven penetration into the recording material, or high-temperature offset occurs. The present disclosure provides a toner and a method for producing the toner that have excellent low-temperature fixability and suppresses uneven penetration into the recording paper and high-temperature offset. [Means for solving the problem]
[0007] The present disclosure provides a toner having toner particles containing a binder resin and boric acid, The binder resin contains an amorphous resin and a crystalline polyester resin, the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The toner has a boric acid content of 0.10% by mass or more and 10.00% by mass or less.
[0008] The present disclosure also provides a method for producing a toner having toner particles containing a binder resin and boric acid, the method comprising the steps of: The binder resin contains an amorphous resin and a crystalline polyester resin, The method for producing the toner comprises the following steps (1) to (3): (1) a mixing step of mixing an amorphous resin particle dispersion containing the amorphous resin and a crystalline polyester resin particle dispersion containing the crystalline polyester resin; (2) an aggregation step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having In the fusion step (3), boric acid is present in the aggregates, the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The present invention relates to a method for producing a toner, in which the content of boric acid in the toner is from 0.10% by mass to 10.00% by mass.
[0009] The present disclosure also provides a method for producing a toner having toner particles containing a binder resin and boric acid, the method comprising the steps of: The binder resin contains an amorphous resin and a crystalline polyester resin, The method for producing the toner comprises the following steps (1) to (3): (1) a mixing step of mixing an amorphous resin particle dispersion containing the amorphous resin and a crystalline polyester resin particle dispersion containing the crystalline polyester resin; (2) an aggregation step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having The toner production method includes a step of adding borax in any one of steps (1) to (3), the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The present invention relates to a method for producing a toner, in which the content of boric acid in the toner is from 0.10% by mass to 10.00% by mass. Effect of the Invention
[0010] According to the present disclosure, a toner that has excellent low-temperature fixing properties and suppresses uneven penetration into recording paper and high-temperature offset can be obtained. [Brief description of the drawings]
[0011] [Figure 1] Example of a device for measuring triboelectric charge DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.
[0013] As mentioned above, there is a method for increasing the content of crystalline polyester resin to improve low-temperature fixability, but this may cause uneven penetration into recording paper and high-temperature offset. Therefore, toner designs have been made to suppress the content of crystalline polyester resin to a level that does not cause these problems. Note that "high-temperature offset" refers to the phenomenon in which a part of the toner image adheres to the surface of the fixing device member because the temperature of the heating roller is too high, and is fixed onto the recording material in the next rotation.
[0014] The present inventors conducted extensive research to solve these problems, and as a result, discovered that in a toner containing an amorphous resin, a crystalline polyester resin, and boric acid, the above problems can be solved by appropriately controlling the content of the crystalline polyester resin and the content of boric acid.
[0015] The present disclosure provides a toner having toner particles containing a binder resin and boric acid, The binder resin contains an amorphous resin and a crystalline polyester resin, the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The toner has a boric acid content of 0.10% by mass or more and 10.00% by mass or less.
[0016] Boric acid is expressed as B(OH)3 and has a hydroxyl group. When crystalline polyester resin and boric acid are used together, it is thought that the hydroxyl group of boric acid and the ester group of the crystalline polyester resin will form a hydrogen bond. In particular, since the toner melts and deforms during fixing, the folded structure of the main chain of the crystalline polyester resin loosens and at the same time, boric acid diffuses into the toner, and it is believed that the boric acid and the crystalline polyester resin are sufficiently mixed together, making it easier to form hydrogen bonds. As a result, the sharp melting properties of the crystalline polyester resin are maintained while excessive melting of the crystalline polyester resin is suppressed even at high temperatures, and high-temperature offset resistance is also good even when the temperature of the heating roller is high.
[0017] In addition, generally, when the content of crystalline polyester resin in a toner is high, the toner has excellent sharp melting properties, but is more susceptible to the influence of the heating state of the recording material during fixing. That is, even on the same recording material, there is a partial temperature difference during fixing, so that the penetration state into the recording material is uneven, which results in gloss unevenness. However, with the above toner, the higher the temperature, the more the mixing of the crystalline polyester resin and boric acid inside the toner is promoted, and a more significant effect is exhibited, so that the influence of the temperature difference on the recording material can be reduced and gloss unevenness can be suppressed.
[0018] These effects can only be obtained when the toner contains appropriate amounts of crystalline polyester resin and boric acid. The issue of gloss unevenness occurs even when the content of crystalline polyester resin is small. For example, when the content of amorphous polyester resin is large, the mixing speed with boric acid during fixing is slow, and the above effects cannot be obtained.
[0019] Furthermore, the inventors believe that even when the toner is stored at around room temperature, the crystalline polyester resin and boric acid form hydrogen bonds, thereby suppressing the molecular movement of the low-melting point component that reduces the heat-resistant storage stability, thereby improving the heat-resistant storage stability.
[0020] Specifically, the content of boric acid in the toner is 0.10% by mass or more and 10.00% by mass or less. If the content is less than 0.10% by mass, the effect of suppressing excessive melting of the crystalline polyester resin cannot be obtained, and high-temperature offset and gloss unevenness occur. If the content is more than 10.00% by mass, pseudo-crosslinking due to hydrogen bonding with the crystalline polyester resin progresses, and sharp melt performance cannot be obtained. In addition, the state of boric acid inside the toner becomes uneven, and gloss unevenness occurs.
[0021] The content of boric acid in the toner is preferably 1.00% by mass or more and 9.00% by mass or less, and more preferably 2.00% by mass or more and 8.00% by mass or less.
[0022] The content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less. If the content of the crystalline polyester resin is less than 30.00% by mass, the amount of crystalline resin is so small that sufficient sharp melt performance cannot be obtained, and mixing with boric acid does not proceed sufficiently during fixing, resulting in gloss unevenness. If the content of the crystalline polyester resin is more than 80.00% by mass, hydrogen bonds with boric acid remain in only a part of the crystalline polyester resin, and fixing occurs before sufficient hydrogen bonds are formed, resulting in high-temperature offset and gloss unevenness. In addition, the chargeability and durability are reduced. The content of the crystalline polyester resin in the toner is preferably 30.00% by mass or more and 70.00% by mass or less, and more preferably 40.00% by mass or more and 60.00% by mass or less.
[0023] In addition, when the content of boric acid in the toner is X% by mass and the content of crystalline polyester resin in the toner is Y% by mass, it is preferable that the ratio of X to Y (X / Y) is 0.025 or more and 0.170 or less. By setting the ratio of boric acid to crystalline polyester resin within the above range, the balance of hydrogen bonds between boric acid and crystalline polyester resin during fixing is improved, low-temperature fixing property and high-temperature offset resistance are improved, and gloss unevenness can be further suppressed. More preferably, X / Y is 0.040 or more and 0.130 or less.
[0024] Boric acid may be present in the toner particles in the form of unsubstituted boric acid, and may be used in the form of an organic boric acid, a borate salt, a borate ester, or the like when used as a raw material.
[0025] When the toner is produced in an aqueous medium, it is preferable to add it as a borate from the viewpoint of reactivity and production stability, and specific examples thereof include sodium tetraborate, ammonium borate, etc., and borax is particularly preferably used. Borax is expressed as a decahydrate of sodium tetraborate Na2B4O7, and changes to boric acid in an acidic aqueous solution, so borax is preferably used when the toner is used in an acidic environment in an aqueous medium.
[0026] The toner particles preferably have a core-shell structure having a core particle containing a crystalline polyester resin and a shell containing an amorphous resin on the surface of the core particle. The core-shell structure reduces the exposure of the crystalline polyester resin to the surface, and in particular suppresses contamination of members caused by the low melting point component of the crystalline polyester resin, thereby improving durability. The core particles may contain an amorphous resin in addition to the crystalline polyester resin. Preferably, the core particles contain a crystalline polyester resin and an amorphous resin.
[0027] The mass ratio of the core particles to the shell is preferably 70:30 to 95:5, more preferably 80:20 to 95:5. Within this range, sufficient low-temperature fixability can be obtained due to the sharp melting property that is a characteristic of the crystalline polyester resin. The shell does not necessarily need to cover the entire core particles, and some of the core particles may be exposed.
[0028] It is more preferable that the core particles of the toner particles contain boric acid. The presence of boric acid inside the core particles makes it easier to form hydrogen bonds with the crystalline polyester resin, thereby improving high-temperature offset resistance and durability, and further suppressing gloss unevenness.
[0029] <Binding resin> The toner contains a binder resin, and the binder resin contains an amorphous resin and a crystalline polyester resin. By containing the amorphous resin in addition to the crystalline polyester resin, contamination of components is prevented.
[0030] <Amorphous resin> The amorphous resin is not particularly limited, but examples thereof include styrene-acrylic resin, epoxy resin, polyester resin, polyurethane resin, polyamide resin, cellulose resin, polyether resin, mixed resins or composite resins thereof. Styrene-acrylic resin and polyester resin are preferred because they are inexpensive, easily available, and have excellent low-temperature fixing properties. Polyester resin is more preferred. The polyester resin is prepared by selecting and combining suitable polycarboxylic acids, polyols, hydroxycarboxylic acids, etc., and subjecting the resulting resin to a known process such as an ester exchange process or a polycondensation process. Preferably, the polyester resin comprises a condensation polymer of a dicarboxylic acid and a diol.
[0031] Polycarboxylic acids are compounds containing two or more carboxy groups in one molecule. Among them, dicarboxylic acids are compounds containing two carboxy groups in one molecule and are preferably used.
[0032] Examples of the acid include oxalic acid, succinic acid, glutaric acid, maleic acid, adipic acid, β-methyladipic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, fumaric acid, citraconic acid, diglycolic acid, cyclohexane-3,5-diene-1,2-carboxylic acid, hexahydroterephthalic acid, malonic acid, pimelic acid, suberic acid, phthalic acid, isophthalic acid, terephthalic acid, tetrachlorophthalic acid, chlorophthalic acid, nitrophthalic acid, p-carboxyphenylacetic acid, p-phenylenediacetic acid, m-phenylenediacetic acid, o-phenylenediacetic acid, diphenylacetic acid, diphenyl-p,p'-dicarboxylic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, anthracenedicarboxylic acid, and cyclohexanedicarboxylic acid.
[0033] Examples of polyvalent carboxylic acids other than the dicarboxylic acids include trimellitic acid, trimesic acid, pyromellitic acid, naphthalene tricarboxylic acid, naphthalene tetracarboxylic acid, pyrene tricarboxylic acid, pyrene tetracarboxylic acid, itaconic acid, glutaconic acid, n-dodecyl succinic acid, n-dodecenyl succinic acid, isododecyl succinic acid, isododecenyl succinic acid, n-octyl succinic acid, n-octenyl succinic acid, etc. These may be used alone or in combination of two or more.
[0034] A polyol is a compound containing two or more hydroxyl groups in one molecule. Among them, a diol is a compound containing two hydroxyl groups in one molecule, and is preferably used.
[0035] Specifically, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1, Examples of the bisphenols include 14-eicosanedecanediol, dipropylene glycol, polyethylene glycol, polypropylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,4-butenediol, neopentyl glycol, polytetramethylene glycol, hydrogenated bisphenol A, bisphenol A, bisphenol F, bisphenol S, and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the above bisphenols.
[0036] Among these, preferred are alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols, and particularly preferred are alkylene oxide adducts of bisphenols and their combined use with alkylene glycols having 2 to 12 carbon atoms. Examples of the alkylene oxide adducts of bisphenol A include the compounds represented by the following formula (A). [ka]
[0037] (In formula (A), each R is independently an ethylene or propylene group, each of x and y is an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.) The alkylene oxide adduct of bisphenol A is preferably a propylene oxide adduct and / or an ethylene oxide adduct of bisphenol A. More preferably, it is a propylene oxide adduct. The average value of x+y is preferably 1 or more and 5 or less.
[0038] Examples of trihydric or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, hexamethylolmelamine, hexaethylolmelamine, tetramethylolbenzoguanamine, tetraethylolbenzoguanamine, sorbitol, trisphenol PA, phenol novolac, cresol novolac, alkylene oxide adducts of the above trihydric or higher polyphenols, etc. These may be used alone or in combination of two or more.
[0039] The glass transition temperature (Tg) of the amorphous resin is preferably within a range of 40° C. to 75° C. The content of the amorphous resin in the toner is preferably from 10.00% to 60.00% by mass, more preferably from 15.00% to 50.00% by mass, and even more preferably from 15.00% to 45.00% by mass.
[0040] <Crystalline polyester resin> The crystalline polyester resin is a polyester resin that exhibits crystallinity and has a clear endothermic peak, i.e., a melting point, in an endothermic curve obtained by differential scanning calorimetry (DSC). Specifically, it is a resin that has a peak with a half-width of 15°C or less in an endothermic curve heated at a heating rate of 10°C / min. In addition, the amorphous resin is a resin that does not have a melting point in the endothermic curve described above.
[0041] The crystalline polyester resin is preferably, for example, a condensation polymer of a divalent or higher polyvalent carboxylic acid and a divalent or higher polyhydric alcohol. A crystalline polyester resin made mainly from an aliphatic dicarboxylic acid and an aliphatic diol is preferred because it is easy to obtain a desired melting point and has a high degree of crystallinity, and a condensation polymer of an aliphatic dicarboxylic acid and an aliphatic diol is more preferred.
[0042] Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,15-pentadecanediol, 1,16-hexadecanediol, dipropylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, octamethylene glycol, nonamethylene glycol, decamethylene glycol, dodecamethylene glycol, neopentyl glycol, and 1,4-butadiene glycol. Preferably, it is at least one monomer selected from the group consisting of α,ω-linear aliphatic diols having 2 to 16 carbon atoms.
[0043] Examples of polycarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, tridecanedicarboxylic acid, tetradecanedicarboxylic acid, pentadecanedicarboxylic acid, hexadecanedicarboxylic acid, heptadecanedicarboxylic acid, octadecanedicarboxylic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, itaconic acid, isophthalic acid, terephthalic acid, n-dodecylsuccinic acid, n-dedecenylsuccinic acid, cyclohexanedicarboxylic acid, and anhydrides or lower alkyl esters of these acids. Preferably, it is at least one monomer selected from the group consisting of α,ω-straight-chain aliphatic dicarboxylic acids having from 2 to 14 carbon atoms, and anhydrides or lower alkyl esters of these acids.
[0044] Methods for obtaining a crystalline polyester resin include a method in which a monomer is divided, one side is condensed to a certain extent, and then the remaining monomer is added and further condensed, and a method in which a low molecular weight crystalline polyester resin and a high molecular weight crystalline polyester resin are synthesized and melt-mixed in a ratio that results in a desired molecular weight distribution.
[0045] The weight average molecular weight Mw of the crystalline polyester resin is preferably 12000 to 45000, and more preferably 15000 to 25000. Within this range, the dispersibility within the toner particles and the viscosity when melted are excellent, which is preferable from the viewpoint of low-temperature fixability. The melting point of the crystalline polyester resin is preferably from 55.0° C. to 90.0° C., and more preferably from 60.0° C. to 80.0° C., from the viewpoints of developability and fixability.
[0046] The crystalline polyester resin has a crystalline polyester moiety, and the ester group concentration of the crystalline polyester moiety defined by the following formula is preferably 3.50 mmol / g or more and 10.00 mmol / g or less. [Ester group concentration (mmol / g)]=[Number of moles of ester groups in the crystalline polyester moiety] / [Molecular weight of the crystalline polyester moiety]
[0047] Within the above range, an effective interaction occurs between the crystalline polyester resin and the borax, and the high-temperature offset resistance is further improved. This is believed to be because boric acid is more easily introduced into the folded structure of the main chain of the crystalline polyester resin. The ester group concentration is more preferably 4.00 mmol / g or more and 8.00 mmol / g or less. In addition, when the crystalline polyester resin is a block polymer described later, it is preferable that the ester group concentration of the crystalline polyester portion is within the above range. The crystalline polyester portion is a portion that can form a lamellar structure in the crystalline polyester resin. For example, the crystalline polyester portion can be formed by a condensation polymer of an aliphatic dicarboxylic acid and an aliphatic diol.
[0048] The crystalline polyester resin is preferably a block polymer containing a crystalline polyester segment and an amorphous polyester segment. The crystalline polyester segment preferably has a structure represented by the following formula (1): In formula (1), m is an integer of 6 to 14, and n is an integer of 6 to 16. [ka]
[0049] The above-mentioned structure improves the dispersibility of the crystalline polyester resin within the toner, suppressing uneven distribution, thereby improving durability. In addition, charge leakage is suppressed, improving charging properties.
[0050] The crystalline polyester moiety preferably has, as a repeating unit, a structure in which a dicarboxylic acid having an alkylene group with 6 to 14 carbon atoms is condensed with a diol having an alkylene group with 6 to 16 carbon atoms. The crystalline polyester moiety preferably has the structure based on the repeating unit in an amount of 90% by mass or more and 100% by mass or less, based on the total mass of the crystalline polyester moiety. The structure represented by the above formula (1) can be obtained by condensation of a dicarboxylic acid and a diol.
[0051] As the dicarboxylic acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, etc. can be used. As the diol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, and the like can be used.
[0052] Next, the amorphous polyester portion will be described. The resin used to form the amorphous polyester portion preferably has a weight average molecular weight (Mw) of 4000 or more and 15000 or less. More preferably, it is 8000 or more and 13000 or less. When Mw is within the above range, the strength of the resin is increased, improving durability, and the viscosity increase of the crystalline polyester resin tends to be suppressed, resulting in excellent low-temperature fixability. In addition, the resin used to form the amorphous polyester portion preferably has a glass transition temperature (Tg) within the range of 40.0 to 75.0°C.
[0053] The resin used to form the amorphous polyester moiety can be selected from the polyvalent carboxylic acids, polyols, hydroxycarboxylic acids, etc. listed in the polyester resins described above and used in combination. The method for producing a block polymer having a crystalline polyester moiety and an amorphous polyester moiety is not particularly limited, and a known method can be used. For example, a crystalline polyester resin and an amorphous polyester resin can be synthesized separately, and then the two are reacted to obtain a block polymer.
[0054] The mass ratio of the crystalline polyester portion to the amorphous polyester portion in the crystalline polyester resin (crystalline polyester portion: amorphous polyester portion) is preferably 40:60 to 95:5, more preferably 45:55 to 80:20.Within this range, sufficient low-temperature fixability can be obtained due to the sharp melting property that is a characteristic of the crystalline polyester portion.
[0055] <Release agent> The toner particles may contain a wax as a release agent. Examples of such wax include the following: Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or their block copolymers; waxes mainly composed of fatty acid esters such as carnauba wax; partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax; saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; brassidic acid unsaturated fatty acids such as oleostearic acid, valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, montanic acid and alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, lauric acid amide; saturated fats such as methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene bisstearic acid amide acid bisamides; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0056] Among these waxes, from the viewpoint of improving low-temperature fixing property and fixing separation property, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax, and more preferred are hydrocarbon waxes from the viewpoint of further improving high-temperature offset resistance.
[0057] The wax content is preferably 3 to 20 parts by mass per 100 parts by mass of the binder resin. In addition, the peak temperature of the maximum endothermic peak of the wax in the endothermic curve during temperature rise measured by a differential scanning calorimetry (DSC) device is preferably 45° C. to 140° C. When the peak temperature of the maximum endothermic peak of the wax is within the above range, the toner can more easily achieve both storage stability and high-temperature offset resistance.
[0058] <Coloring agent> The toner may contain a colorant, if necessary. Examples of the colorant include the following. Examples of black colorants include carbon black, yellow colorants, magenta colorants, and cyan colorants that are toned to black. As colorants, pigments may be used alone, or dyes and pigments may be used in combination. From the viewpoint of image quality of full-color images, it is preferable to use dyes and pigments in combination.
[0059] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Dyes for magenta toner include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; and CI Disperse Violet 1; C. I. Basic dyes such as Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; Basic dyes such as CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0060] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Dyes for cyan toners include CI Solvent Blue 70. Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0061] These colorants can be used alone or in mixture, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner. The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin.
[0062] <Charge control agent> The toner particles may contain a charge control agent. Any known charge control agent can be used as the charge control agent. In particular, a charge control agent that can charge quickly and stably maintain a constant charge amount is preferred. As the charge control agent that controls the toner particles to have a negative charge, the following can be mentioned. Organometallic compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. Other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.
[0063] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: nigrosine and nigrosine modifications such as fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts analogous thereto, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake forming agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents. These charge control agents can be used alone or in combination of two or more. The amount of these charge control agents added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less with respect to 100.00 parts by mass of the binder resin.
[0064] <Toner manufacturing method> The method for producing the toner is not particularly limited, and may be a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, or the like. Known methods such as a dispersion polymerization method can be used. In any of the methods for producing toner particles, it is preferable to obtain toner particles by adding a boric acid source when mixing the raw materials. Here, the toner is preferably produced by the method shown below. That is, the toner is preferably produced by an emulsion aggregation method.
[0065] Preferably, the method for producing the toner comprises the following steps (1) to (3): (1) a mixing step of mixing an amorphous resin particle dispersion containing an amorphous resin and a crystalline polyester resin particle dispersion containing a crystalline polyester resin; (2) an aggregation step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together having In the fusion step (3), boric acid is present in the aggregates, The content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The content of boric acid in the toner is 0.10% by mass or more and 10.00% by mass or less.
[0066] When the toner is produced by the emulsion aggregation method, the boric acid is easily uniformly dispersed in the crystalline polyester resin, and therefore, the crystalline polyester resin and the boric acid are mixed throughout the toner particles during fixing, which is preferable. The emulsion aggregation method will be described in detail below.
[0067] <Emulsification aggregation method> The emulsion aggregation method is a method in which an aqueous dispersion of fine particles made of the constituent materials of toner particles, which are sufficiently small relative to the target particle size, is prepared in advance, and the fine particles are aggregated in an aqueous medium until they reach the particle size of the toner particles, and the resin is fused by heating or the like to produce toner particles. That is, in the emulsion aggregation method, toner particles are manufactured through a dispersion process in which a fine particle dispersion liquid made of the constituent materials of the toner particles is prepared, an aggregation process in which fine particles made of the constituent materials of the toner particles are aggregated and the particle size is controlled until the particle size becomes the same as that of the toner particles, a fusion process in which the resin contained in the obtained aggregated particles is fused, a subsequent cooling process, a metal removal process in which the obtained toner is filtered and excess polyvalent metal ions are removed, a filtration / washing process in which the toner particles are washed with ion-exchanged water or the like, and a process in which moisture is removed from the washed toner particles and they are dried.
[0068] <Step of preparing a resin particle dispersion (dispersion step)> The resin microparticle dispersion liquid can be prepared by a known method, but is not limited to these methods.The known methods include, for example, emulsion polymerization method, self-emulsification method, phase inversion emulsification method in which resin is emulsified by adding aqueous medium to the resin solution dissolved in organic solvent, and forced emulsification method in which resin is forcedly emulsified by high temperature treatment in aqueous medium without using organic solvent. Specifically, the binder resin is dissolved in an organic solvent capable of dissolving it, and a surfactant or a basic compound is added. In this case, if the binder resin is a crystalline resin having a melting point, it may be dissolved by heating it to above its melting point. Then, while stirring with a homogenizer or the like, an aqueous medium is slowly added to precipitate the resin fine particles. Thereafter, the solvent is removed by heating or reducing pressure to prepare an aqueous dispersion of the resin fine particles. Any organic solvent can be used to dissolve the resin as long as it can dissolve the resin, but it is preferable to use an organic solvent that forms a homogeneous phase with water, such as toluene, from the viewpoint of suppressing the generation of coarse powder.
[0069] The surfactant used in the emulsification is not particularly limited, but examples thereof include anionic surfactants such as sulfate ester salts, sulfonate salts, carboxylate salts, phosphate esters, and soap-based surfactants; and cationic surfactants such as amine salts and quaternary ammonium salts. nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, polyhydric alcohols, etc. The surfactants may be used alone or in combination of two or more. Examples of the basic compound used in the dispersion step include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. The basic compound may be used alone or in combination of two or more. The 50% particle size (D50) based on volume distribution of the binder resin particles in the aqueous dispersion of the resin particles is preferably 0.05 μm to 1.0 μm, and more preferably 0.05 μm to 0.4 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it becomes easy to obtain toner particles with a volume average particle size of 3 μm to 10 μm, which is appropriate for toner particles. The 50% particle size (D50) based on volume distribution is measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso).
[0070] <Colorant particle dispersion> The colorant particle dispersion liquid used as required can be prepared by the known methods described below, but is not limited to these methods. The colorant, the aqueous medium, and the dispersant can be mixed by a known mixer such as a stirrer, an emulsifier, or a disperser. The dispersant used here can be a known one such as a surfactant or a polymer dispersant. Although both the surfactant and the polymer dispersant can be removed in the washing step described below, the surfactant is preferred from the viewpoint of washing efficiency. Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soap-based surfactants; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, nonionic surfactants or anionic surfactants are preferred. A nonionic surfactant and an anionic surfactant may be used in combination. The surfactant may be used alone or in combination of two or more. The concentration of the surfactant in the aqueous medium is preferably 0.5% by mass to 5% by mass.
[0071] The content of the colorant particles in the colorant particle dispersion is not particularly limited, but is preferably 1% by mass to 30% by mass with respect to the total mass of the colorant particle dispersion. From the viewpoint of dispersibility of the colorant in the toner finally obtained, the dispersed particle size of the colorant particles in the aqueous dispersion of the colorant is preferably 0.5 μm or less in terms of the 50% particle size (D50) based on volume distribution. For the same reason, it is preferable that the 90% particle size (D90) based on volume distribution is 2 μm or less. The dispersed particle size of the colorant particles dispersed in the aqueous medium is measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso). Known mixers such as stirrers, emulsifiers, and dispersers used when dispersing a colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint shakers. These may be used alone or in combination.
[0072] <Release agent (aliphatic hydrocarbon compound) fine particle dispersion> If necessary, a dispersion of releasing agent particles may be used. The dispersion of releasing agent particles can be prepared by the following known methods, but is not limited to these methods. The release agent microparticle dispersion is prepared by adding the release agent to an aqueous medium containing a surfactant, heating the mixture above the melting point of the release agent, and then using a homogenizer (such as an M.T. It can be prepared by dispersing the material into particles using a dispersing machine (such as the Clearmix W Motion manufactured by Knik) or a pressure discharge type dispersing machine (such as the Gaulin Homogenizer manufactured by Gaulin), and then cooling the resulting mixture below its melting point. The particle size of the dispersion of the release agent particles in the aqueous dispersion of the release agent is preferably 50% particle size (D50) based on volume distribution of 0.03 μm to 1.0 μm, more preferably 0.1 μm to 0.5 μm. It is also preferable that no coarse particles of 1 μm or more exist. By setting the particle size of the release agent fine particle dispersion within the above range, the release agent can be finely dispersed in the toner, the exudation effect during fixing can be maximized, and good separation properties can be obtained. The particle size of the release agent fine particle dispersion dispersed in the aqueous medium can be measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150: manufactured by Nikkiso).
[0073] <Mixing process> In the mixing step, a mixture is prepared by mixing the resin fine particle dispersion and, if necessary, at least one of the release agent fine particle dispersion and the colorant fine particle dispersion, using a known mixing device such as a homogenizer or a mixer.
[0074] <Step of forming aggregate particles (aggregation step)> In the aggregating step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates having a desired particle size. At this time, an aggregating agent is added and mixed, and at least one of heating and mechanical power is appropriately applied as necessary to form aggregates in which the resin fine particles and at least one of the release agent fine particles and the colorant fine particles are aggregated as necessary.
[0075] Examples of the flocculant include organic flocculants such as cationic surfactants of quaternary salts and polyethyleneimine; inorganic metal salts such as sodium sulfate, sodium nitrate, sodium chloride, calcium chloride, calcium nitrate; inorganic ammonium salts such as ammonium sulfate, ammonium chloride, ammonium nitrate; and inorganic flocculants such as divalent or higher metal complexes. It is also possible to add an acid to lower the pH and cause soft flocculation, and for example, sulfuric acid, nitric acid, etc. can be used.
[0076] The coagulant may be added in the form of either a dry powder or an aqueous solution dissolved in an aqueous medium, but in order to cause uniform coagulation, it is preferable to add it in the form of an aqueous solution. The addition and mixing of the coagulant is preferably carried out at a temperature equal to or lower than the glass transition temperature or melting point of the resin contained in the mixed liquid. By carrying out mixing under this temperature condition, the coagulation proceeds relatively uniformly. The mixing of the coagulant into the mixed liquid can be carried out using a known mixing device such as a homogenizer or a mixer. The coagulation step is a step of forming aggregates of the toner particle size in an aqueous medium. The volume average particle size of the aggregates produced in the coagulation step is preferably 3 μm to 10 μm. The volume average particle size can be measured using a particle size distribution analyzer (Coulter Multisizer III: manufactured by Coulter) by the Coulter method.
[0077] <Step of Obtaining Dispersion Liquid Containing Toner Particles (Fusion Step)> In the fusion step, the dispersion containing the aggregates obtained in the aggregation step is first subjected to termination of aggregation under stirring in the same manner as in the aggregation step by adding an aggregation terminator such as a base capable of adjusting the pH, a chelating compound, or an inorganic salt compound such as sodium chloride. After the dispersion state of the aggregated particles in the dispersion liquid becomes stable due to the action of the aggregation terminator, the aggregated particles are fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the binder resin, and the particle size is adjusted to a desired particle size. The 50% particle size (D50) based on volume of the toner particles is preferably 3 μm to 10 μm.
[0078] <Cooling process> If necessary, in the cooling step, the temperature of the dispersion liquid containing the toner particles obtained in the fusion step can be cooled to a temperature lower than at least one of the crystallization temperature and the glass transition temperature of the binder resin. By cooling to a temperature lower than at least one of the crystallization temperature and the glass transition temperature, it is possible to prevent the generation of coarse particles. The specific cooling rate can be 0.1°C / min to 50°C / min.
[0079] <Post-processing process> In the toner manufacturing method, after the cooling step, post-treatment steps such as a washing step, a solid-liquid separation step, and a drying step may be performed. By performing the post-treatment steps, toner particles in a dry state are obtained.
[0080] <External addition process> The obtained toner particles may be used as a toner as they are. In the external addition step, inorganic fine particles are externally added to the toner particles obtained in the drying step, as necessary. Specifically, inorganic fine particles such as silica, and resin fine particles such as vinyl resin, polyester resin, and silicone resin are preferably added by applying a shear force in a dry state.
[0081] In the toner production method, boric acid is preferably present in the following steps (1) to (3). The toner production method preferably includes a step of adding a boric acid source (preferably borax) in any of steps (1) to (3). More preferably, the boric acid source is added and mixed in step (1). (1) a mixing step of mixing an amorphous resin particle dispersion containing an amorphous resin and a crystalline polyester resin particle dispersion containing a crystalline polyester resin; (2) an aggregation step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) a fusion step of heating the aggregates to fuse them together In the aggregation step, a boric acid source may be added during the step.
[0082] The boric acid source may be boric acid or a compound that can be converted to boric acid by pH control during toner production. For example, a boric acid source may be added and controlled so that boric acid is contained in the aggregates at least in the step (3).
[0083] The boric acid may be present in the aggregate in an unsubstituted state. The boric acid source is preferably at least one selected from the group consisting of organic boric acid, borate salts, borate esters, etc. When the toner is produced in an aqueous medium, it is preferable to add the borate salt in view of reactivity and production stability. Specifically, the boric acid source more preferably includes at least one selected from the group consisting of sodium tetraborate, ammonium borate, etc., and even more preferably is borax.
[0084] Borax is represented by the decahydrate of sodium tetraborate Na2B4O7, and is converted to boric acid in an acidic aqueous solution, so borax is preferably used when used in an acidic environment in an aqueous medium. It may be added in the form of either a dry powder or an aqueous solution dissolved in an aqueous medium, but it is preferable to add it in the form of an aqueous solution in order to cause uniform aggregation.
[0085] The addition of borax may be performed in any of the above steps (1) to (3). Preferably, borax is added and mixed in the mixing step (1). More preferably, borax is added and mixed in the mixing step (1). The aqueous solution is mixed to make the dispersion acidic. The concentration of the aqueous solution may be appropriately changed depending on the concentration to be contained in the toner, and is, for example, 1 to 20% by mass. In order to convert it to boric acid, it is preferable to make the pH acidic before, during, or after the mixing. For example, it may be controlled to 1.5 to 5.0, preferably 2.0 to 4.0.
[0086] <Analysis> <Separation of crystalline polyester resin and measurement of the content of crystalline polyester resin in toner> The toner is placed in chloroform and left to stand at 25°C for several hours, then thoroughly shaken and allowed to stand for another 12 hours or more until no more aggregates remain in the sample. The resulting solution is subjected to silica gel column chromatography to separate and recover the crystalline polyester component, which is then dried. As the developing solvent, chloroform, hexane, methanol, etc. are used, and the mixing ratio is adjusted to isolate the crystalline polyester component. The content of the crystalline polyester resin in the toner is calculated from the mass of the obtained crystalline polyester resin.
[0087] <Calculation of Ester Group Concentration in Crystalline Polyester Moiety in Crystalline Polyester Resin> The ester group concentration indicates the proportion of ester groups in the crystalline polyester, and is defined by the following formula. [Ester group concentration (mmol / g)]=[Number of moles of ester groups in the crystalline polyester moiety] / [Molecular weight of the crystalline polyester moiety] Polyester resins are generally obtained by the reaction of polycarboxylic acids with polyhydric alcohols, and ester bonds are formed by dehydration condensation between the carboxyl groups in the polycarboxylic acids and the hydroxyl groups in the polyhydric alcohols. The molar number of ester groups in the crystalline polyester moiety in the above formula and the molecular weight of the crystalline polyester moiety are determined by the molar number of carboxyl groups in the polycarboxylic acids and the hydroxyl groups in the polyhydric alcohols when the crystalline polyester is synthesized. Specifically, if the polycarboxylic acid is a divalent carboxylic acid represented by formula (I) and the polyhydric alcohol is a divalent alcohol represented by formula (II), the crystalline polyester obtained by formula (I) and formula (II) will be represented by formula (III). HOOC-R 1 -COOH (I) H.O.R. 2 -OH (II) -(-OCO-R 1 -COO-R 2 -) n - (III) R 1 and R 2 is any hydrocarbon group, for example, R 1 is a linear alkylene group having 6 to 14 carbon atoms, and R 2 represents a linear alkylene group having 6 to 16 carbon atoms. The number of moles of ester groups in the above formula (III) is the average of the number of moles of carboxy groups in the above formula (I) and the number of moles of hydroxy groups in the above formula (II), and is therefore two. Furthermore, if the molecular weight of the above formula (I) is m1 and the molecular weight of the above formula (II) is m2, then the molecular weight m3 of the above formula (III) is m1 + m2 - 18 × (average of the number of moles of carboxy groups and the number of moles of hydroxy groups) = m3. Therefore, the ester group concentration in the above formula (III) is expressed as follows: [ester group concentration] = (average of the number of moles of carboxy groups and the number of moles of hydroxy groups) / m3. In addition, when two or more polycarboxylic acids or two or more polyhydric alcohols are used in combination, the calculation may be made from the average number of moles and molecular weight of the carboxyl groups of each polycarboxylic acid and the average number of moles and molecular weight of the hydroxyl groups of each polyhydric alcohol. Furthermore, in order to determine the ester group concentration from a crystalline polyester, for example, 1 It can be calculated by H-NMR (nuclear magnetic resonance) measurement, etc. Specifically, the ester group concentration is calculated from the ratio of the peak of the hydrogen atom derived from the carbon of the alkyl portion to the peak of the hydrogen atom derived from the carbon adjacent to the ester group. In order to measure the temperature of the endothermic peak top, the ester group concentration and content, etc., from the crystalline polyester contained in the toner, the crystalline polyester is extracted from the toner. The crystalline polyester can be extracted from the toner by the above-mentioned method.
[0088] <Measurement of weight average molecular weight (Mw) and number average molecular weight (Mn) of toner or resin, etc.> The molecular weight of the toner, resin, etc. is measured by gel permeation chromatography (GPC) as follows. First, a sample such as a toner is dissolved in tetrahydrofuran (THF) at room temperature. The resulting solution is then filtered through a solvent-resistant membrane filter with a pore size of 0.2 μm, "Maeshori Disk" (manufactured by Tosoh Corporation), to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8% by mass. This sample solution is used to perform measurements under the following conditions. Equipment: High-speed GPC equipment "HLC-8220GPC" [Tosoh Corporation] Column: 2 columns of LF-604 [Showa Denko Co., Ltd.] Eluent:THF Flow rate: 0.6mL / min Oven temperature: 40℃ Sample injection volume: 0.020mL In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.
[0089] <Measurement of boric acid content in toner> The boric acid contained in the toner is identified and the content thereof is measured by the following method. Whether or not a toner contains boric acid can be confirmed by using infrared absorption spectroscopy. Specifically, an appropriate amount of toner or toner particle sample resin is mixed with potassium bromide (KBr) and molded. This is used to measure the infrared absorption spectrum. Boric acid has a vibration frequency of 1380 cm -1 Since there is an absorption wavelength in this portion, it is possible to confirm the presence of boric acid. In addition, elemental analysis can be performed by energy dispersive X-ray spectroscopy (EDX) using a transmission electron microscope (TEM) to confirm whether boron derived from boric acid is present in the observed portion of the cross section.
[0090] The boric acid content in the toner is measured by fluorescent X-rays and obtained by the calibration curve method. Specifically, an aluminum ring (inner diameter 40 mm, outer diameter 43 mm, height 5 mm) is set on the sample molding die of a semi-automatic MiniPress machine (Specac). 3 g of toner is placed in it and pressurized for 1 minute at a pressure of 15 t to produce a pellet for measurement. A pellet molded to a thickness of about 3 mm and a diameter of about 40 mm is used. Measurements are performed under the following conditions using a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. In addition, boron is detected by a proportional counter (PC). The acceleration voltage and current of the X-ray generator are set to 32 kV and 125 mA, respectively. Measurements are performed under the above conditions, boron is identified based on the peak position of the obtained X-rays, and the counting rate (unit: cps), which is the number of X-ray photons per unit time, is measured. In addition, the amount of boric acid (mass%) in the toner is calculated from a separately prepared calibration curve for boric acid.
[0091] If necessary, in order to eliminate the influence of external additives, the measurement can be performed using toner particles from which external additives have been removed by the following method. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Add 31 g of concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.). Add 1.0 g of toner to this, and break up the toner clumps with a spatula or similar. Shake the centrifuge tube at 300 strokes per minute (spm) in a shaker (AS-1N, sold by AS ONE Corporation) for 20 minutes. After shaking, transfer the solution to a glass tube for a swing rotor (50 mL) and separate it in a centrifuge (H-9R, manufactured by Kokusan Corporation) at 3,500 rpm for 30 minutes. This operation separates the toner particles from the external additives. Visually check that the toner particles and the aqueous solution are sufficiently separated, and collect the toner particles that have separated to the top layer with a spatula or similar. The collected toner particles are filtered through a vacuum filter, and then dried in a dryer for at least one hour to obtain a sample for measurement. This operation is carried out multiple times to ensure the required amount.
[0092] <Measuring method of melting point and half width of crystalline polyester resin> The melting point and half width of the crystalline polyester resin are measured under the following conditions using a DSC Q1000 (manufactured by TA Instruments). Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc are used to correct the temperature of the device's detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, 5 mg of sample is precisely weighed and placed in an aluminum pan, and differential scanning calorimetry is performed. An empty silver pan is used as a reference. The peak temperature of the maximum endothermic peak in the first heating process is taken as the melting point (°C). The half-width is a value automatically calculated by the analysis software. Note that if there are multiple peaks, the peak with the greatest amount of endothermic heat is used to determine the value.
[0093] <Method for measuring the glass transition temperature Tg of amorphous resin> The glass transition temperature Tg was measured using a differential scanning calorimeter "Q2000" (TA Instrument Measurements are performed using a 3000K quartz crystal analyzer (manufactured by NTS). The melting points of indium and zinc are used to correct the temperature of the detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, 5 mg of sample is weighed out and placed in an aluminum pan, and an empty aluminum pan is used as a reference, and measurements are performed at a heating rate of 10°C / min. During the temperature rise process, a specific heat change is obtained in the temperature range of 40° C. to 100° C. The intersection point between the line midway between the baselines before and after the specific heat change occurs and the differential thermal curve is defined as the glass transition temperature of the resin.
[0094] <Measurement of toner particle size> The particle size of the toner particles can be measured by the pore electrical resistance method. For example, it can be measured and calculated using the "Coulter Counter Multisizer 3" and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). Precision particle size distribution measuring device using the pore electrical resistance method (product name: Coulter Counter Mu We use a multisizer (Multisizer 3) and dedicated software (Product name: Beckman Coulter Multisizer 3 Version 3.51, manufactured by Beckman Coulter, Inc.) with an aperture diameter of 100 μm, and measure with an effective number of measurement channels of 25,000. We analyze the measurement data and perform calculations.
[0095] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example ISOTON manufactured by Beckman Coulter. II (trade name) can be used. Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using (standard particle 10.0 μm, manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. Also, set the current to 1600 μA, the gain to 2, and the electrolyte to ISOTON II (trade name), and perform the measurement. Check the aperture tube flush after setting. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0096] The specific measurement method is as follows. (1) Place the electrolytic solution in a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3. Pour in approximately 200 mL of liquid, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) About 30 mL of the aqueous electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a diluted solution of Contaminon N (trade name) (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments, manufactured by Wako Pure Chemical Industries, Ltd.) diluted three times by mass with ion-exchanged water is added thereto. (3) An ultrasonic disperser (product name: Ultrasonic Dispersion) with two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. n System Tetora150, manufactured by Nikkaki Bios Co., Ltd. Add a specified amount of ion-exchanged water and approximately 2 mL of Contaminon N (trade name) to the water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1). EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following formulations, "parts" are by weight unless otherwise specified.
[0098] <Production Example of Crystalline Polyester Resin 1> 153.0 parts of 1,6-hexanediol, 300.0 parts of 1,10-decanedicarboxylic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 4 hours. Thereafter, the temperature was raised to 220°C while the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain crystalline polyester resin 1. The melting point (Tm) of this crystalline polyester resin 1 was 71.2°C, and the number average molecular weight (Mn) was 5100. Crystalline polyester The properties of Resin 1 are shown in Table 1.
[0099] <Production Example of Crystalline Polyester Resin 2> 371.0 parts of 1,18-octadecanediol, 483.0 parts of 1,20-eicosanedicarboxylic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 4 hours. Thereafter, the temperature was raised to 220°C, and the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain crystalline polyester resin 2. The melting point of crystalline polyester resin 2 was 74.0°C, and the number average molecular weight was 5800. The properties of crystalline polyester resin 2 are shown in Table 1.
[0100] <Production Example of Crystalline Polyester Resin 3> In a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen inlet device, 80.0 parts of ethylene glycol, 172.0 parts of glutaric acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added and reacted at 190°C for 4 hours. Thereafter, the temperature was raised to 220°C while the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain crystalline polyester resin 3. The melting point of crystalline polyester resin 3 was 86.2°C, and the number average molecular weight was 4200. The properties of crystalline polyester resin 3 are shown in Table 1.
[0101] <Production Example of Crystalline Polyester Resin 4> 335.0 parts of 1,16-hexadecanediol, 446.0 parts of 1,18-octadecanedicarboxylic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 4 hours. Thereafter, the temperature was raised to 220°C, and the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain crystalline polyester resin 4. The melting point of crystalline polyester resin 4 was 77.3°C, and the number average molecular weight was 6100. The properties of crystalline polyester resin 4 are shown in Table 1.
[0102] <Production Example of Crystalline Polyester Resin 5> 80.0 parts of ethylene glycol, 264.0 parts of sebacic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 4 hours. Thereafter, the temperature was raised to 220°C while the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain crystalline polyester resin 5. Crystalline polyester resin 5 had a melting point of 82.1°C and a number average molecular weight of 3. The viscosity was 200. The properties of Crystalline Polyester Resin 5 are shown in Table 1.
[0103] <Production Example of Crystalline Polyester Resin 6> In a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, 153.0 parts of 1,6-hexanediol, 300.0 parts of 1,10-decanedicarboxylic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added and reacted at 190°C for 2 hours. Thereafter, the temperature was raised to 220°C while the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain a crystalline polyester resin A. The melting point (Tm) of this crystalline polyester resin A was 70.5°C, and the number average molecular weight (Mn) was 3000.
[0104] In a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube, and a nitrogen introducing device, 108.0 parts of bisphenol A-ethylene oxide (2 moles) adduct, 368.0 parts of bisphenol A-propylene oxide (2 moles) adduct, 83.0 parts of terephthalic acid, 78.0 parts of isophthalic acid, 27.0 parts of dodecenyl succinic anhydride, and 0.3 parts of dibutyltin oxide were added and reacted at 180°C for 4 hours and further at 220°C under reduced pressure for 2 hours to obtain amorphous polyester resin A. The weight average molecular weight (Mw) of this amorphous polyester resin A was 1200. The molecular weight (Mn) was 6,100, and the glass transition temperature (Tg) was 57°C.
[0105] In a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube and a nitrogen introducing device, 100.0 parts of the above-mentioned amorphous polyester resin A, 100.0 parts of the above-mentioned crystalline polyester resin A, and 0.1 parts of dibutyltin oxide were added and reacted at 190 ° C for 2 hours, and then the temperature was raised to 240 ° C and the pressure in the system was gradually reduced, and the reaction was carried out at 150 Pa to obtain crystalline polyester resin 6. The crystalline polyester resin 6 was a block polymer, and had a weight average molecular weight (Mw) of 19300, a number average molecular weight (Mn) of 13500, and a melting point (Tm) of 64.2 ° C. The properties of the crystalline polyester resin 6 are shown in Table 1.
[0106] <Production Example of Crystalline Polyester Resin 7> 335.0 parts of 1,16-hexadecanediol, 300.0 parts of 1,10-decanedicarboxylic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 2 hours. Thereafter, the temperature was raised to 220°C, and the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain a crystalline polyester resin B. The melting point (Tm) of this crystalline polyester resin B was 81.0°C, and the number average molecular weight (Mn) was 4000.
[0107] In a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube and a nitrogen introducing device, 108.0 parts of bisphenol A-ethylene oxide (2 moles) adduct, 368.0 parts of bisphenol A-propylene oxide (2 moles) adduct, 83.0 parts of terephthalic acid, 78.0 parts of isophthalic acid, 27.0 parts of dodecenyl succinic anhydride, and 0.3 parts of dibutyltin oxide were added and reacted at 180 ° C. for 4 hours and further at 220 ° C. under reduced pressure for 2 hours to obtain amorphous polyester resin B. The weight average molecular weight (Mw) of this amorphous polyester resin B was 12000, the number average molecular weight (Mn) was 6100, and the glass transition temperature (Tg) was 57 ° C.
[0108] In addition, 100.0 parts of amorphous polyester resin B, 100.0 parts of crystalline polyester resin B, and 0.1 parts of dibutyltin oxide were added to a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190 ° C for 2 hours. The temperature was then raised to 240 ° C, and the pressure in the system was gradually reduced, and the reaction was carried out at 150 Pa to obtain crystalline polyester resin 7. Crystalline polyester resin 7 was a block polymer, and had a weight average molecular weight (Mw) of 21500, a number average molecular weight (Mn) of 15100, and a melting point (Tm) of 78.0 ° C. The properties of crystalline polyester resin 7 are shown in Table 1.
[0109] <Production Example of Crystalline Polyester Resin 8> 153.0 parts of 1,6-hexanediol, 227.0 parts of suberic acid, and 0.3 parts of titanium (IV) isopropoxide as an esterification catalyst were added to a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190°C for 2 hours. Thereafter, the temperature was raised to 220°C, and the pressure in the system was gradually reduced, and a polycondensation reaction was carried out at 150 Pa to obtain a crystalline polyester resin C. The melting point (Tm) of this crystalline polyester resin C was 73.9°C, and the number average molecular weight (Mn) was 3600.
[0110] In a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube and a nitrogen introducing device, 108.0 parts of bisphenol A-ethylene oxide (2 moles) adduct, 368.0 parts of bisphenol A-propylene oxide (2 moles) adduct, 83.0 parts of terephthalic acid, 78.0 parts of isophthalic acid, 27.0 parts of dodecenyl succinic anhydride, and 0.3 parts of dibutyltin oxide were added and reacted at 180 ° C. for 4 hours and further at 220 ° C. under reduced pressure for 2 hours to obtain amorphous polyester resin C. The weight average molecular weight (Mw) of this amorphous polyester resin C was 12000, the number average molecular weight (Mn) was 6100, and the glass transition temperature (Tg) was 57 ° C.
[0111] In addition, 100.0 parts of amorphous polyester resin C, 100.0 parts of crystalline polyester resin C, and 0.1 parts of dibutyltin oxide were added to a reaction vessel equipped with another stirring device, a temperature sensor, a cooling tube, and a nitrogen introducing device, and reacted at 190 ° C for 2 hours. The temperature was then raised to 240 ° C, and the pressure in the system was gradually reduced, and the reaction was carried out at 150 Pa to obtain crystalline polyester resin 8. Crystalline polyester resin 8 was a block polymer, and had a weight average molecular weight (Mw) of 22300, a number average molecular weight (Mn) of 16200, and a melting point (Tm) of 71.5 ° C. The properties of crystalline polyester resin 8 are shown in Table 1.
[0112] <Production Example of Amorphous Resin 1> A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube and a nitrogen inlet device was charged with 108.0 parts of bisphenol A-ethylene oxide (2 moles) adduct, 368.0 parts of bisphenol A-propylene oxide (2 moles) adduct, 83.0 parts of terephthalic acid, 78.0 parts of isophthalic acid, 27.0 parts of dodecenyl succinic anhydride, and 0.3 parts of dibutyltin oxide, and reacted at 180 ° C. for 4 hours and further at 220 ° C. under reduced pressure for 2 hours to obtain amorphous polyester resin Amorphous Resin 1. The weight average molecular weight (Mw) of this amorphous resin 1 was 12000, the number average molecular weight (Mn) was 6100, and the glass transition temperature (Tg) was 57 ° C.
[0113] <Production of Dispersion of Crystalline Polyester Resin 1> Crystalline polyester resin 1: 100 parts was put into a Cavitron CD1010 (made by Eurotech Co., Ltd.) and dispersed using a disperser modified to a high-temperature, high-pressure type. Specifically, the composition ratio was 79% ion-exchanged water, 1% anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd.: Neogen RK) (as an active ingredient), and the solid concentration was 20%, and the pH was adjusted to 8.5 with ammonia, the rotor rotation speed was 60 Hz, and the pressure was 5 kg / cm. 2 The Cavitron was operated under the conditions of 140° C., and heating by a heat exchanger to obtain a crystalline polyester resin 1 dispersion having a number average particle size of 160 nm.
[0114] <Production of Dispersions of Crystalline Polyester Resins 2 to 8> Dispersion was carried out in the same manner as in the production example of the dispersion of crystalline polyester resin 1, except that the crystalline polyester resin 1 was changed to crystalline polyester resins 2 to 8, to obtain dispersions of crystalline polyester resins 2 to 8.
[0115] <Production Example of Dispersion of Amorphous Resin 1> Amorphous resin 1: 100 parts was put into a Cavitron CD1010 (made by Eurotech Co., Ltd.) and dispersed using a disperser modified to a high-temperature, high-pressure type. Specifically, the composition ratio was 79% ion-exchanged water, 1% anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd.: Neogen RK) (as an active ingredient), and the solid concentration was 20%, and the pH was adjusted to 8.5 with ammonia, the rotor rotation speed was 60 Hz, and the pressure was 5 kg / cm. 2 The Cavitron was operated under the conditions of heating at 140° C. using a heat exchanger to obtain a dispersion of amorphous resin 1 having a number average particle size of 150 nm.
[0116] <Production Example of Release Agent Microparticle Dispersion> Release agent HNP-51 (manufactured by Nippon Seiro) 100 parts Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5 parts 395 parts of ion-exchanged water The above materials were weighed and placed in a mixing vessel equipped with a stirrer, then heated to 90°C and circulated through a Clearmix W Motion (M Technique) for 60 minutes to perform dispersion processing. The dispersion processing conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min
[0117] After the dispersion treatment, the mixture was cooled to 40°C under cooling treatment conditions of a rotor rotation speed of 1000 r / min, a screen rotation speed of 0 r / min, and a cooling rate of 10°C / min, thereby obtaining an aqueous dispersion (release agent fine particle dispersion) with a release agent fine particle concentration of 20 mass%. The 50% particle size (D50) based on volume distribution of the release agent (aliphatic hydrocarbon compound) fine particles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.
[0118] <Production of colorant particle dispersion> Coloring agent 50.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 7.5 parts Ion-exchanged water 442.5 parts The above materials were weighed, mixed, dissolved, and dispersed for approximately 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain an aqueous dispersion (colorant particle dispersion) containing dispersed colorant particles with a concentration of 10% by mass. The 50% particle size (D50) based on the volume distribution of the colorant fine particles was measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.
[0119] <Preparation of Silica Microparticles 1> Fumed silica (product name: AEROSIL380S, specific surface area by BET method: 380 m 2 / g, number average particle diameter of primary particles 7 nm, manufactured by Nippon Aerosil Co., Ltd.) to 10.0 parts of polydimethylsiloxane (viscosity = 100 mm 2 / s) was sprayed into the mixture, and stirring was continued for 30 minutes. Thereafter, the temperature was raised to 300° C. with stirring, and stirring was continued for another 2 hours to prepare silica microparticles 1.
[0120] <Toner 1 Manufacturing Example> [Toner production by emulsion aggregation method] Dispersion of crystalline polyester resin 1 (20%) 185.0 parts Dispersion of amorphous resin 1 (20%) 315.0 parts Release agent microparticle dispersion (20%) 40.0 parts Colorant microparticle dispersion (10%) 80.0 parts Ion-exchanged water 160.0 parts ·10.0% by mass borax aqueous solution 2.0 parts (Borax; Sodium tetraborate decahydrate Na2B4O7·10H2O, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) The above materials were put into a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% aqueous nitric acid solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles of 6.2 μm were formed, the pH was adjusted to 9.0 using a 5% aqueous sodium hydroxide solution. Then, the mixture was heated to 75°C while continuing to stir. The aggregated particles were fused by holding at 75°C for 1 hour. The mixture was then cooled to 50°C and held there for 3 hours to promote crystallization of the polymer. It was then cooled to 25°C, filtered and separated into solid and liquid, and washed with ion-exchanged water. After washing, the mixture was dried in a vacuum dryer to obtain toner particles 1 with a weight average particle size (D4) of 6.3 μm.
[0121] External addition was performed on the above toner particles 1. 100.0 parts of toner particles 1 and 1.5 parts of silica fine particles 1 were dry mixed for 5 minutes using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 4-1.
[0122] <Production examples of toners 2-18 and 34-37> Toners 2 to 18 and 34 to 37 were obtained in the same manner as in Production Example 1 of Toner 1, except that the types and amounts of the dispersion of crystalline polyester resin 1 and the dispersion of amorphous resin 1, and the concentration and amount of the borax aqueous solution were changed as shown in Table 2. The toner physical properties are shown in Tables 4-1 and 4-2.
[0123] <Production Example of Toner 19> [Toner production by emulsion aggregation method] Dispersion of crystalline polyester resin 1 (20%) 185.0 parts Dispersion of amorphous resin 1 (20%) 265.0 parts Release agent microparticle dispersion (20%) 40.0 parts Colorant microparticle dispersion (10%) 80.0 parts Ion-exchanged water 160.0 parts ·10.0% by mass borax aqueous solution 20.0 parts The above materials were put into a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (manufactured by IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% aqueous nitric acid solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles of 6.0 μm were formed, 50.0 parts of a dispersion of amorphous resin 1 was added, and the volume average particle size of the aggregated particles was confirmed again, and when aggregated particles of 6.1 μm were formed, the pH was adjusted to 9.0 using a 5% aqueous sodium hydroxide solution. Then, the mixture was heated to 75°C while continuing to stir. The aggregated particles were fused by holding at 75°C for 1 hour. The mixture was then cooled to 50°C and held there for 3 hours to promote crystallization of the polymer. It was then cooled to 25°C, filtered, and separated into solid and liquid, and then washed with ion-exchanged water. After washing, the mixture was dried using a vacuum dryer to obtain toner particles 19 having a weight average particle size (D4) of 6.3 μm. The same external additions as in Toner 1 were made to Toner Particle 19 to obtain Toner 19. The physical properties of Toner 19 are shown in Table 4-1.
[0124] <Production example of toner 20-30> Toners 20 to 30 were obtained by the same procedure as in Production Example 19 of Toner 19, except that the types and amounts of the dispersion of crystalline polyester resin 1 and the dispersion of amorphous resin 1, and the concentration and amount of the borax aqueous solution were changed as shown in Table 3. The toner physical properties are shown in Tables 4-1 and 4-2.
[0125] <Toner 31 Manufacturing Example> [Toner production by emulsion aggregation method] Dispersion of crystalline polyester resin 1 (20%) 185.0 parts Dispersion of amorphous resin 1 (20%) 265.0 parts Release agent microparticle dispersion (20%) 40.0 parts Colorant microparticle dispersion (10%) 80.0 parts Ion-exchanged water 160.0 parts The above materials were put into a round stainless steel flask and mixed. Then, the mixture was dispersed for 10 minutes at 5000 rpm using a homogenizer Ultra Turrax T50 (manufactured by IKA). A 1.0% aqueous solution of nitric acid was added to adjust the pH to 3.0, and the mixture was then heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The volume average particle size of the formed aggregated particles was appropriately confirmed using a Coulter Multisizer III, and when aggregated particles of 6.0 μm were formed, 20.0 parts of a 10.0% by mass aqueous solution of borax was added. After the addition of the aqueous solution of borax, 50. 0 parts of sodium hydroxide was added, and the volume average particle size of the aggregated particles was confirmed again. When aggregated particles with a particle size of 6.1 μm were formed, the pH was adjusted to 9.0 using a 5% aqueous sodium hydroxide solution. Then, while continuing to stir, the mixture was heated to 75° C. The mixture was then held at 75° C. for 1 hour to fuse the aggregated particles.
[0126] The mixture was then cooled to 50°C and held there for 3 hours to promote crystallization of the polymer. It was then cooled to 25°C, filtered and separated into solid and liquid, and washed with ion-exchanged water. After washing, the mixture was dried using a vacuum dryer to obtain toner particles 31 having a weight average particle size (D4) of 6.3 μm. The same external additions as for toner 1 were made to toner particles 31, to obtain toner 31. The physical properties of toner 31 are shown in Table 4-2.
[0127] <Production Example of Toner 32> Toner 32 was obtained in the same manner as in Production Example 19 of Toner 19, except that 20.0 parts of the 10.0 mass% borax aqueous solution was changed to 13.0 parts of a 10.0 mass% boric acid aqueous solution (boric acid; boric acid H3BO3 manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.). The physical properties of Toner 32 are shown in Table 4-2.
[0128] <Toner 33 Manufacturing Example> [Toner production by pulverization method] Crystalline polyester resin 1 37.0 parts Amorphous resin 1 63.0 parts CI Pigment Blue 15:3 8.0 parts Release agent (Nippon Seiro Co., Ltd.: HNP-51, melting point: 74°C) 8.0 parts Charge control agent (T-77: manufactured by Hodogaya Chemical Co., Ltd.) 2.0 parts Boric acid powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 1.3 parts The above materials were premixed in an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.), and then melt-kneaded using a twin-screw kneading extruder (Model PCM-30 manufactured by Ikegai Iron Works Co., Ltd.). The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then pulverized with a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.). The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect, and toner particles 33 having a weight average particle size (D4) of 7.0 μm were obtained. The same external additions as in Toner 1 were made to Toner Particle 33 to obtain Toner 33. The physical properties of Toner 33 are shown in Table 4-2.
[0129] <Example 1> Toner 1 was subjected to the following evaluations. <1> Evaluation of low temperature fixability The process cartridge filled with toner was left in a normal temperature and humidity (N / N) environment (23°C, 60% RH) for 48 hours. Using an LBP652C modified to operate even without the fixing unit, an unfixed image was printed with an image pattern in which 9 10mm x 10mm square images were evenly arranged on the entire transfer paper. The amount of toner on the transfer paper was 0.80mg / cm. 2The transfer paper was Fox River Bond (90 g / m 2 ) was used.
[0130] The fixing unit was an external fixing unit that was removed from the LBP652C and was made to operate outside the laser beam printer. The fixing temperature of the external fixing unit was set to 110 The temperature was raised from 0.degree. C. in 10° C. increments, and fixing was performed under the conditions of a process speed of 220 mm / sec.
[0131] Fixing image at 50g / cm 2 The sample was rubbed with Silbon paper (Lenz Cleaning Paper "dasper(R)" (Ozu Paper Co. Ltd.)) under a load of 1000 g. The temperature at which the density loss rate before and after rubbing became 10% or less was defined as the fixing start temperature, and the low-temperature fixing property was evaluated according to the following criteria. The evaluation results are shown in Table 5. [Evaluation Criteria] A: Fixing start temperature is 110℃ B: Fixing start temperature is 120℃ C: Fixing start temperature is 130℃ D: Fixing start temperature is 140°C or higher
[0132] <2> Evaluation of electrostatic charge The difference in charge amount in a low temperature, low humidity (LL) environment and a high temperature, high humidity (HH) environment was evaluated by the following method: 0.7 g and 9.3 g of toner and a specified carrier (Japan Imaging Society standard carrier: spherical carrier N-01 with surface-treated ferrite core) were placed in a plastic bottle with a lid, and left for 5 days in an LL environment with a temperature of 15°C and a relative humidity of 10% and an HH environment with a temperature of 35.0°C and a relative humidity of 85%.
[0133] The plastic bottle containing the carrier and toner is closed, and shaken for 1 minute with a shaker (YS-LD, manufactured by Yayoi Co., Ltd.) at a speed of 4 reciprocations per second to charge the developer consisting of the toner and carrier. Next, the amount of triboelectric charge is measured using a device for measuring triboelectric charge shown in FIG. 1. In FIG. 1, 0.5 g to 1.5 g of the developer is placed in a metal measurement container 2 having a screen 3 with a mesh size of 20 μm at the bottom, and a metal lid 4 is placed. The mass of the entire measurement container 2 at this time is precisely weighed and defined as W1 (g). Next, in the suction device 1 (the part in contact with the measurement container 2 is at least an insulator), suction is performed from the suction port 7, and the air flow control valve 6 is adjusted to set the pressure of the vacuum gauge 5 to 2.5 kPa. Suction is performed for 2 minutes in this state, and the toner is sucked and removed. The potential of the electrometer 9 at this time is defined as V (V). Here, 8 is a capacitor with a capacity of C (mF). The mass of the entire measurement container after suction is precisely weighed and defined as W2 (g). The amount of triboelectric charge Q (mC / kg) of this sample is calculated using the following formula. Frictional charge of sample Q(mC / kg)=C×V / (W1-W2) The triboelectric charge of the sample immediately after shaking in the LL environment was QL (mC / kg), and the triboelectric charge in the HH environment was QH (mC / kg), and the ratio QH / QL was used as an index of environmental stability. The evaluation results are shown in Table 5. [Evaluation Criteria] A: QH / QL is 0.85 or more B: QH / QL is 0.80 or more and less than 0.85 C: QH / QL is 0.75 or more and less than 0.80 D: QH / QL is less than 0.75
[0134] <3> Evaluation of high temperature offset resistance <1> In the test, an unfixed toner image (0.6 mg / cm2) measuring 2.0 cm in length and 15.0 cm in width was used as the unfixed image. 2 ) was formed at a position 1.0 cm from the top end in the paper feed direction. The fixing temperature of the external fixing unit was raised in 10°C increments from 110°C, and fixing was performed under the conditions of a process speed of 200 mm / sec. The temperature at which high-temperature offset occurred was defined as the high-temperature offset temperature. <1> The fixing width was calculated using the fixing start temperature obtained in the above and the following formula. Fixing width (℃) = (High temperature offset resistance temperature - Fixing start temperature) The evaluation results are shown in Table 5. (Evaluation Criteria) A: Fixing width is 60℃ or more B: Fixing width is 50℃ or more and less than 60℃ C: Fixing temperature is 30℃ or higher and less than 50℃ D: Fixing width is less than 30°C
[0135] <4> Evaluation of paper penetration <1> In the test, images fixed at a temperature 30°C higher than the fixing start temperature were measured at all points on each image using a handy gloss meter PG-3D (manufactured by Nippon Denshoku Industries Co., Ltd.) at a light incidence angle of 75°, and the difference between the maximum and minimum values was taken as gloss unevenness, which was used as an index of penetration into paper. The evaluation results are shown in Table 5. [Evaluation Criteria] A: Gloss unevenness is less than 4 B: Gross unevenness is 4 or more and less than 7 C: Gloss unevenness is 7 or more and less than 10 D: Gloss unevenness is 10 or more
[0136] <5> durability A commercially available Canon printer LBP9200C was used to evaluate durability. The LBP9200C uses one-component contact development, and a toner regulating member regulates the amount of toner on the developer carrier. The cartridge for evaluation was a commercially available cartridge in which the toner was removed, the inside was cleaned with an air blower, and then filled with 150 g of the toner to be evaluated. The above cartridge was installed in the cyan station, and dummy cartridges were installed in the other stations to perform the evaluation. The evaluation was carried out under normal temperature and humidity conditions (temperature 23°C / humidity 60% RH). A4 CS-680 (grammage 68g / cm 2 After continuously outputting 12,000 sheets of 1% printed images using a developing device, the developing container was disassembled and the surface and ends of the toner carrier were visually inspected. The evaluation results are shown in Table 5. (Evaluation Criteria) A: There are absolutely no circumferential streaks on the surface or edges of the toner carrier caused by toner destruction or fusion, or by foreign matter being caught between the toner regulating member and the toner carrier. B: A small amount of foreign matter was found between the toner carrier and the toner end seal. C: 1 to 4 circumferential streaks are observed at the edge. D: Five or more circumferential stripes are visible throughout the entire area.
[0137] <Examples 2 to 33> Toners 2 to 33 were evaluated in the same manner as in Example 1. The results are shown in Table 5.
[0138] <Comparative Examples 1 to 4> Toners 34 to 37 were evaluated in the same manner as in Example 1. The results are shown in Table 5.
[0139] [Table 1]
[0140] [Table 2]
[0141] [Table 3]
[0142] In Tables 4-1 and 4-2, the crystalline polyester ratio is the content of the crystalline polyester resin in the toner (Y mass%), and the boric acid ratio is the content of the boric acid in the toner (X mass%). The boric acid / crystalline polyester ratio is the ratio of X to Y (X / Y). The structure indicates the mass ratio of the core and shell resins. [Table 4-1]
[0143] [Table 4-2]
[0144] [Table 5] [Explanation of symbols]
[0145] 1: Aspirator, 2: Measurement container, 3: Screen, 4: Lid, 5: Vacuum gauge, 6: Air flow control valve, 7: Suction port, 8: Condenser, 9: Electrometer
Claims
1. A toner having toner particles containing a binder resin and boric acid, The binder resin contains an amorphous resin and a crystalline polyester resin, the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The toner has a boric acid content of 0.10% by mass or more and 10.00% by mass or less.
2. The crystalline polyester resin has a crystalline polyester moiety, 2. The toner according to claim 1, wherein the ester group concentration of the crystalline polyester moiety defined by the following formula is 3.50 mmol / g or more and 10.00 mmol / g or less. [Ester group concentration (mmol / g)]=[number of moles of ester groups in the crystalline polyester moiety] / [molecular weight of the crystalline polyester moiety]
3. 3. The toner according to claim 1, wherein the content of the boric acid in the toner is from 1.00% by mass to 9.00% by mass.
4. the toner particles include core particles containing the crystalline polyester resin; and A shell containing the amorphous resin on the surface of the core particle.
4. The toner according to claim 1, which has a core-shell structure having the formula:
5. The toner according to claim 4 , wherein said core particles comprise said boric acid.
6. the crystalline polyester resin is a block polymer containing a crystalline polyester portion and an amorphous polyester portion, 6. The toner according to claim 1, wherein the crystalline polyester moiety has a structure represented by the following formula (1): (In formula (1), m is an integer from 6 to 14, and n is an integer from 6 to 16.)
7. 7. The toner according to claim 1, wherein, when a content of the boric acid in the toner is X% by mass and a content of the crystalline polyester resin in the toner is Y% by mass, a ratio of X to Y (X / Y) is 0.025 or more and 0.170 or less.
8. A method for producing a toner having toner particles containing a binder resin and boric acid, comprising the steps of: The binder resin contains an amorphous resin and a crystalline polyester resin, The method for producing the toner comprises the following steps (1) to (3): (1) a mixing step of mixing an amorphous resin particle dispersion containing the amorphous resin and a crystalline polyester resin particle dispersion containing the crystalline polyester resin; (2) an aggregating step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) A fusion step of heating the aggregates to fuse them together having In the fusion step (3), boric acid is present in the aggregates, the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The toner manufacturing method according to the present invention is characterized in that the content of the boric acid in the toner is from 0.10% by mass to 10.00% by mass.
9. A method for producing a toner having toner particles containing a binder resin and boric acid, comprising the steps of: The binder resin contains an amorphous resin and a crystalline polyester resin, The method for producing the toner comprises the following steps (1) to (3): (1) a mixing step of mixing an amorphous resin particle dispersion containing the amorphous resin and a crystalline polyester resin particle dispersion containing the crystalline polyester resin; (2) an aggregating step of aggregating the fine particles contained in the amorphous resin fine particle dispersion and the crystalline polyester resin fine particle dispersion to form aggregates; and (3) A fusion step of heating the aggregates to fuse them together having The toner manufacturing method includes a step of adding borax in any one of steps (1) to (3), the content of the crystalline polyester resin in the toner is 30.00% by mass or more and 80.00% by mass or less, The toner manufacturing method according to the present invention is characterized in that the content of the boric acid in the toner is from 0.10% by mass to 10.00% by mass.
10. 10. The method for producing a toner according to claim 8, further comprising the step of adding borax in the mixing step (1) and mixing to make the dispersion acidic.
Citation Information
Patent Citations
Electrophotographic toner
JP1996202072A
Method of manufacturing electrophotographic developer
JP2001228650A
Electrostatic charge image developing toner, electrostatic charge image developer and image forming method
JP2009300848A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge and image formation apparatus
JP2012042539A
Image forming method
JP2013020113A